Capacidade para o trabalho e fatores associados em profissionais de atividades sedentárias - Maganhini, Claudia Bernardes (2011)
The ability to work is influenced by several factors such as socio-demographic variables, working conditions, lifestyle and general health. Considering these points, the aim of this study was to identify the level of capacity for work and analyze the associated factors in employees from a company which provides service of water supply and sewage treatment in the city of Bauru. A cross-sectional study involving 176 workers was conducted. Those workers completed a multidimensional questionnaire, the Nordic musculoskeletal symptoms and the level of capacity for work. Distribution was made of absolute and relative frequencies and a bivariated analysis using Pearson's test. The questionnaire revealed that the population of workers studied was male, their average education level was elementary school and they were predominant married workers aged between 20 and 35. The workers reported pain mainly in skeletal muscles in the lower back, knees and spine. The assessment of capacity for work found that 51.2% of respondents had a moderate ICT, and 34.7% had a high ICT. Individuals, who reported higher prevalence of musculoskeletal pain, showed lower rates of capacity for work. However in analyses of the association between aspects of general health and the level of work ability, it was observed that workers who reported health problems showed lower rates. In relation to absence at work, the individuals who had not been absent reported better level of work ability. This study concluded that there was a significant association (P< 0,05) with musculoskeletal symptoms, health problems and absence from work and therefore a interdisciplinary, intersectional and multidisciplinary is necessary in order to positively affect the work process and worker health.